Peran Content Marketing dalam Membangun Brand Awareness pada Produk Skincare Kahf - Firmansyah, Ihsan; Kulsum, Resya Siti; Permana, Agil; Yudawisastra, Helin Garlinia (Journal of Multidisciplinary Inquiry in Science, Technology and Educational Research, 2025)
The development of social media has encouraged companies to adopt content marketing strategies as a means of building brand awareness. Instagram has become a widely used platform for brands to deliver marketing messages in a visual and interactive manner. This study aims to analyze the role of content marketing in building brand awareness of Kahf skincare products through Instagram. The research employs a qualitative descriptive method using digital observation of the Instagram account @kahfeveryday during the period from September to December 25, 2025. Data were collected through content documentation, captions, and audience interactions, and then analyzed using the Miles and Huberman model. The findings indicate that Kahf’s Instagram content is dominated by educational and promotional posts with consistent brand visuals. However, audience engagement remains relatively low, resulting in brand awareness that is still at the level of brand recognition. This study recommends strengthening more interactive content strategies to enhance brand recall and top-of-mind awareness among audiences.